2021
DOI: 10.3390/photonics8080342
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap on Universal Photonic Biosensors for Real-Time Detection of Emerging Pathogens

Abstract: The COVID-19 pandemic has made it abundantly clear that the state-of-the-art biosensors may not be adequate for providing a tool for rapid mass testing and population screening in response to newly emerging pathogens. The main limitations of the conventional techniques are their dependency on virus-specific receptors and reagents that need to be custom-developed for each recently-emerged pathogen, the time required for this development as well as for sample preparation and detection, the need for biological am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 196 publications
(213 reference statements)
0
3
0
Order By: Relevance
“…Different reactions of certain enzymes with the cells emit photons as a byproduct. The emission of photons during the reaction creates fluorescence that is utilized in the detection process of various pathogens [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…Different reactions of certain enzymes with the cells emit photons as a byproduct. The emission of photons during the reaction creates fluorescence that is utilized in the detection process of various pathogens [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…The examples described above, together with other achievements of AI-supplemented sensing, suggest the beginning of a revolutionary era of intelligent biosensors, extensively discussed in literature (see Refs. [129,[141][142][143][144] for instance). Seemingly, metastructures and metasurfaces will play an important role in the development of those ideas.…”
Section: Chemical and Biological Sensingmentioning
confidence: 99%
“…Among the different sensor modalities, photonic biosensors based on the evanescent field principle have been positioned as an ideal technology, performing ultrasensitive analysis in a label-free and real-time format. [7][8][9] Latest research on labelfree photonic biosensors has demonstrated their excellent capabilities for detection and identification of respiratory virus infections, such as influenza, respiratory syncytial virus, and coronaviruses. 7 For SARS-CoV-2, few studies have been recently published fully addressing the label-free optical biosensing of viral particles, [10][11][12] viral RNA, 13 or viral antigens.…”
Section: Introductionmentioning
confidence: 99%